Analisis Penerapan Good Governance dalam Pengelolaan Dana Bantuan Keuangan Khusus (BKK) di Desa Wolwal Barat, Kecamatan Alor Barat Daya, Kabupaten Alor - Theo Reinhardt Marcelino Bolang; Akhmad Syafruddin; Yohanes J. Nami (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The purpose of this study was to determine the application of good governance principles in the management of special financial assistance funds, which were analyzed through four aspects, namely accountability, participation, transparency and effectiveness & efficiency of the community and all village government officials.The research was conducted in West Wolwal Village, West Alor District, Alor Regency using a qualitative method with an intrinsic case study approach. The data in this study came from structured interviews, observation,documentation with informants who were used as research subjects. Processing research data by analyzing data using data reduction techniques, presenting data, and drawing conclusions and verification.The findings in this study show that the management of special financial assistance funds in West Wolwal Village has been in accordance with the management mechanism in accordance with the Alor Regent Regulation No. 08 of 2020 concerning changes to the Alor Regent Regulation No.24 of 2018. However, in the analysis of good governance principles, it was found that the principle of accountability was in accordance with the principles of good governance, while the principles of participation, transparency and effectiveness & efficiency were not optimally implemented according to the principles of good governance in Wolwal Barat Village.